2010
DOI: 10.1590/s0004-282x2010000300004
|View full text |Cite
|
Sign up to set email alerts
|

Mean intrasellar pressure, visual field, headache intensity and quality of life of patients with pituitary adenoma

Abstract: Intrasellar pressure (ISP) measurement technique has recently opened a new line of research in neuroendocrinology. The absolute and mean ISP values were investigated in 25 patients consecutively operated at the Brasilia University Hospital (DF). These data were correlated with serum prolactin levels, number of visual quadrant affected, tumor size, quality of life (measured through the SF-36 scale) and graded headache (measured through the HIT-6 scale). No correlation was observed. The p values were 0.887; 0.13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 20 publications
(34 reference statements)
3
17
0
Order By: Relevance
“…20 Similarly, this study has found that preoperative headache severity is significantly associated with reduced scores across all SF-36 QOL dimensions, including mental health and general health. These results are intuitive in that patients with the greatest headache severity would suffer the greatest impact of the pain on their daily life and limitations in their individual capabilities.…”
Section: Discussionsupporting
confidence: 54%
“…20 Similarly, this study has found that preoperative headache severity is significantly associated with reduced scores across all SF-36 QOL dimensions, including mental health and general health. These results are intuitive in that patients with the greatest headache severity would suffer the greatest impact of the pain on their daily life and limitations in their individual capabilities.…”
Section: Discussionsupporting
confidence: 54%
“…Several studies have recorded intrasellar pressure in the operating room and reported it to be higher in patients with headache [23][24][25][26]. Validation of this metric as a way of attributing the headache to sellar or parasellar pathology will require confirmation that intrasellar pressure is particularly elevated in patients with postoperative improvement in headache.…”
Section: Discussionmentioning
confidence: 99%
“…In another prospective study by Levy and colleagues, 63 patients initially seen with pituitary tumours were evaluated for headache which was present in 70%, whereas Pereira‐Neto et al . found moderate to severe headache, graded by means of the Headache Impact Test Scale (HIT‐6) in 68% (17/25 patients) consecutive patients undergoing surgery for pituitary adenomas . Gondim and colleagues assessed the presence of headache and headache characteristics (by means of a self‐made questionnaire) in 64 prospective patients with a primary pituitary mass .…”
Section: Prevalence and Clinical Characteristics Of Headache In Pituimentioning
confidence: 99%
“…An increase in tumour size may raise the intrasellar pressure (ISP) . Even though ISP measurements are not available in healthy persons, ‘normal’ ISP was defined in patients with small microadenomas or in patients with empty sella .…”
Section: Pathophysiology Of Headache In Pituitary Diseasementioning
confidence: 99%